Public Costs versus Private Gain: Assessing the Effect of Different Types of Information about Corruption Incidents on Electoral Accountability. Issue 1 (April 2019) - Avenburg, Alejandro
Are voters' attitudes towards corrupt candidates affected by the details they learn about candidates' wrongdoing? This study examines the effect of including different pieces of information emphasising the public costs or private gain of a similar corruption incident on the probability of support for the incumbent mayor's re-election. I use three surveys experiments with online convenience samples of Brazilian subjects. The survey experiments use various vignettes presenting a fictitious Brazilian incumbent mayor with antecedents of misuse of public funds, running for re-election. I manipulate the details that subjects learn on those antecedents to assess whether information on the public costs of the corruption incident or on the candidate's illicit enrichment stimulates a stronger rejection. Additional manipulations are used to test rival hypotheses. Results consistently show that information showing the candidate's illicit enrichment drives a stronger negative response than every alternative treatment.